Effect of a community-based intervention on child nutritional status in Rimi Ward, Kano State, Nigeria - Sulaiman, Saadatu; Ahmad, Auwal A; Shehu, Amina; Imam, Kareemah; Chinyere, Edith K; Galadanchi, Hadiza S; Ishaq, Daha U; Gadanya, Aisha M; Abubakar, Salisu M (World Nutrition, 2025)
BackgroundSuboptimal infant and young child feeding practices significantly contribute to poor child nutritional status, particularly in low-income settings like Nigeria, where high prevalences of undernutrition, including stunting, wasting, and underweight, persist (WHO, 2021; NDHS, 2023). Community-based interventions are crucial for improving nutritional outcomes.ObjectiveThis study evaluates the effect of a community-based intervention, comprising nutrition education, home gardening, and small-scale animal rearing, on the nutritional status of children aged 6-59 months in Rimi Ward, Sumaila LGA, Kano State, Nigeria.MethodsA quasi-experimental study design was employed to assess weight-for-height Z-score (WFH Z-score) and mid-upper arm circumference (MUAC) at baseline and endline after a 6-month intervention period for a cohort of 148 children aged 6-59 months. A multi-stage sampling technique was used; Rimi Ward was purposively selected for its high malnutrition burden. Four community volunteers were recruited and trained for three days to assist with anthropometric measurements (weight, height/length, and MUAC) during baseline and endline data collection. After the baseline assessment, a six-month community-based intervention comprising nutrition education, home gardening, and goat and poultry rearing was implemented. Paired samples t-test was used to determine significant changes in mean WFH Z-score, and Stuart Maxwell tests were used to assess changes in WFH Z-score and MUAC nutritional status categories.ResultsThe socio-demographic profile showed that most caregivers of these children (51.4%) were young mothers aged 16–25 years, with no formal education (59.5%). Most were self-employed or unemployed and incomes were low. The intervention led to significant improvements in child nutritional status. The prevalence of moderate wasting (14.2% to 5.4%) and severe wasting (7.4% to 0.7%) decreased substantially. Similarly, MUAC showed marked reductions in severe acute malnutrition (6.1% to 0%) and moderate acute malnutrition (6.8% to 1.4%), with a corresponding increase in normal nutritional status (87.2% to 98.7% of children) (p